Особенности отражения гендерной идентичности на персональных веб-страницах - Горошко, Елена Игоревна (Харківський національний університет внутрішніх справ, 2006)
Исходя из предположения, что тендер является социальной конструктивисткой категорией, анализируются ресурси и способи "создания" гендерной идентичности в постсоветском секторе Интернета на примере персональних веб-страниц.

Based on the underlying assumption that gender is a social construct, the paper describes gender identity in computer-mediated communication (CMC) on the Net. Thus? it examines the resources and techniques for constructing gender identity on personal web pages and investigates the role of the net as an agent of social change in matters relating to gender.
Feature of reflection gender identity on personal web-pages
Keywords: интернет-коммуникация; виртуальная идентичность; мужской стиль; женский стиль